Factors Affecting the Candidacy for Total Hip Replacement Assessed in 953 Dogs - Erickson, Andrea K.; Orona, Christina E.; Parker, Elizabeth M.; Dyce, Jonathan (VCOT Open, 2025)
To define reasons for delay to canine total hip replacement (THR). Retrospective clinical study of 953 dogs evaluated for THR between 2013 and 2020. Three hundred and fifty-three dogs (37%) proceeded to immediate THR. Reasons for the initial delay in 600 dogs (63%) included: medical management (42%), other orthopaedic conditions (25%), pyoderma (12%), neurologic disease (7%), concurrent medical condition (7%), immature age (3%), prohibitive behaviour (3%), and for lack of advanced imaging requirement (1%). Of the 92% of dogs with hip dysplasia/osteoarthritis (HD/OA), 32% proceeded to THR without delay. One-hundred and thirteen (19%) dogs that were rejected initially, subsequently had THR. The highest percentage returning for THR were those initially rejected for pyoderma (74%), advanced imaging (67%), and skeletal immaturity (35%). The lowest percentage for THR return included concurrent orthopaedic conditions (3%), neurologic disease (1%), and prohibitive behaviour (0%). The most common reason for referral for evaluation for a THR was OA. The majority of dogs were rejected because of incomplete medical management. Immediate THR following primary evaluation is uncommon and common reasons for delay are incomplete medical management, incorrect initial diagnosis, and prohibitive comorbidities.
Keywords: total hip arthroplasty; total hip replacement; hip dysplasia; canine